Suppression of food intake and growth by amino acids in Drosophila: the role of pumpless, a fat body expressed gene with homology to vertebrate glycine cleavage system. - Zinke, I.; Kirchner, C.; Chao, L.C.; Tetzlaff, M.T.; Pankratz, M.J. (Development, 1999)
We have isolated a Drosophila mutant, named pumpless, which is defective in food intake and growth at the larval stage. pumpless larvae can initially feed normally upon hatching. However, during late first instar stage, they fail to pump the food from the pharynx into the esophagus and concurrently begin moving away from the food source. Although pumpless larvae do not feed, they do not show the typical physiologic response of starving animals, such as upregulating genes involved in gluconeogenesis or lipid breakdown. The pumpless gene is expressed specifically in the fat body and encodes a protein with homology to a vertebrate enzyme involved in glycine catabolism. Feeding wild-type larvae high levels of amino acids could phenocopy the feeding and growth defects of pumpless mutants. Our data suggest the existence of an amino acid-dependent signal arising from the fat body that induces cessation of feeding in the larva. This signaling system may also mediate growth transition from larval to the pupal stage during Drosophila development.